Effect of metformin therapy on cardiac function and survival in a volume-overload model of heart failure in rats - Benes, Jan; Kazdova, Ludmila; Drahota, Zdenek; Houstek, Josef; Medrikova, Dasa; Kopecky, Jan; Kovarova, Nikola; Vrbacky, Marek; Sedmera, David; Strnad, Hynek; Kolar, Michal; Petrak, Jiri; et al. (Clinical science (London, England, 2011)
Advanced HF (heart failure) is associated with altered substrate metabolism. Whether modification of substrate use improves the course of HF remains unknown. The antihyperglycaemic drug MET (metformin) affects substrate metabolism, and its use might be associated with improved outcome in diabetic HF. The aim of the present study was to examine whether MET would improve cardiac function and survival also in non-diabetic HF. Volume-overload HF was induced in male Wistar rats by creating ACF (aortocaval fistula). Animals were randomized to placebo/MET (300 mg·kg(-1) of body weight·day(-1), 0.5% in food) groups and underwent assessment of metabolism, cardiovascular and mitochondrial functions (n=6-12/group) in advanced HF stage (week 21). A separate cohort served for survival analysis (n=10-90/group). The ACF group had marked cardiac hypertrophy, increased LVEDP (left ventricular end-diastolic pressure) and lung weight confirming decompensated HF, increased circulating NEFAs (non-esterified 'free' fatty acids), intra-abdominal fat depletion, lower glycogen synthesis in the skeletal muscle (diaphragm), lower myocardial triacylglycerol (triglyceride) content and attenuated myocardial (14)C-glucose and (14)C-palmitate oxidation, but preserved mitochondrial respiratory function, glucose tolerance and insulin sensitivity. MET therapy normalized serum NEFAs, decreased myocardial glucose oxidation, increased myocardial palmitate oxidation, but it had no effect on myocardial gene expression, AMPK (AMP-activated protein kinase) signalling, ATP level, mitochondrial respiration, cardiac morphology, function and long-term survival, despite reaching therapeutic serum levels (2.2±0.7 μg/ml). In conclusion, MET-induced enhancement of myocardial fatty acid oxidation had a neutral effect on cardiac function and survival. Recently reported cardioprotective effects of MET may not be universal to all forms of HF and may require AMPK activation or ATP depletion. No increase in mortality on MET supports its safe use in diabetic HF.
Keywords: metabolismus lipidů; Hemodynamics; krevní glukóza; glykogen; Heart Failure; metformin; velikost orgánu; AMP-Activated Protein Kinase Kinases; Survival Analysis; krysa rodu Rattus; srdeční selhání; Drug Evaluation, Preclinical; analýza přežití; ultrasonografie; Mitochondria, Heart; Organ Size; proteinkinasy; preklinické hodnocení léčiv; potkani Wistar; myokard; Ultrasonography; Protein Kinases; Disease Models, Animal; Rats, Wistar; Lipid Metabolism; Metformin; srdeční mitochondrie; mužské pohlaví; Blood Glucose; zvířata; kinasy AMP aktivovaných proteinkinas; Myocardium; Rats; Animals; hemodynamika; Male; Lung; hypoglykemika; Glycogen; tělesná hmotnost; modely nemocí na zvířatech; Hypoglycemic Agents; plíce; Body Weight